TikTok Shop: How trust and privacy influence generation Z’s purchasing behaviors - Nurdiana Putri; Yadhit Prasetya; Putu Wuri Handayani; Hana Fitriani (Cogent Social Sciences, 2024)
TikTok has implemented e-commerce functions, such as short video media, images, and livestreaming for selling products, that make it a social commerce platform. As an emerging social commerce platform, it is important for TikTok that it evoke trust in its users, so they feel secure in doing transactions. Using trust transfer theory and the theory of security assurance, this current research analyzed how TikTok Shop users’ trust in sellers on the shop as well as their privacy concerns (PCs) influence purchasing behaviors. This study was carried out using a mixed-method method, using a partial least square structural equation model and content analysis, which involved 717 questionnaire respondents and 30 interviews. It found that both cognitive and emotional trust has a significant effect on purchase intention on TikTok Shop, although not all sources of trust building (perceived familiarity, situational normality, trust in a platform, and social interactivity) equally effect on cognitive and emotional trust. This study also found that security-related factors (e.g. having a privacy/security policy, an assurance seal, and a disposition to third-party certification) influenced consumers’ privacy concerns. Trust in a seller and PCs were proven to affect consumers’ shopping intentions, which also influenced their shopping behaviors. This study is expected to guide social commerce providers in improving the actual shopping behavior of consumers, especially in the context of building trust and security.